Tick-Borne Encephalitis sequelae at long-term follow-up: a self-reported case-control study - (:unkn) unknown (WILEY, 2016)
BackgroundTick-borne encephalitis (TBE), caused by the TBE virus (TBEV), is a major neurotropic infection throughout Europe and Asia, with a considerable risk of neurological sequelae. Our aim was to study the symptoms in patients with TBE in Western Gotaland between 1997 and 2012 in the acute phase and at follow-up after 2-15 years (median: 5.5 years). MethodsThe medical records of 96 patients with TBE were studied. Phone-based interviews were held with 92 patients and 58 controls, matched by age, gender and residential area. The Encephalitis Support Group Questionnaire (ESGQ) 2000 was used, further developed with dimensions and scoring 1-4, where a high score is related to better outcome. Patients and controls also answered a written survey regarding functional outcome of sleep (FOSQ). ResultsOf the patients, 35% had a mild disease, 56% moderate and 7.3% severe disease. At the follow-up, patients scored significantly lower than controls in the dimensions of memory/learning, executive functions, vigilance and physical impairments. In addition, the answers concerning tiredness/fatigue, poor concentration/attention, reduced initiative/motivation, balance disturbances, coordination problems, difficulties with short- and long-term memory, learning difficulties and problems with fine motor skills resulted in significantly lower scores in the patients compared with the controls. The patients scored lower than the controls in the FOSQ dimension social outcome. ConclusionsAt the long-term follow-up, the patients scored significantly lower in a diversity of neurocognitive and motor symptoms, in comparison with controls. These sequelae and their pathogenesis should be further explored and specific neurocognitive assessment tests are needed.
Keywords: infections; sleep disorders; EPIDEMIOLOGY; VACCINATION; ETIOLOGY; SWEDEN; AREA